Strategi Komunikasi DISKOMINFOTIK dalam Menyukseskan Acara UMKM Rameune Nagan Raya Expo 2023 - Fahrol Fazal; Said Fadhlain (MUKASI: Jurnal Ilmu Komunikasi, 2024)
The development of micro, small and medium enterprises is one of the state opinions that the government really pays attention to because it is proven by the government's serious attention in developing micro, small and medium enterprises in Indonesia. Naga Raya is a district in Aceh Province, Indonesia with the capital being Suka Makmue. Nagan Raya Regency Diskominfotik is one of the parties that takes part in managing the event and provides information about events that will take place as a form of implementing the work program. This research was studied based on the concept of communication strategy according to Porter (in Nila, 2014), namely planning, implementation and evaluation. This research method is descriptive qualitative. The results of this research, namely Diskominfotik, target information targets for the 2023 Rameune Nagan Raya Expo event, namely MSME actors, entrepreneurs and the general public. Dissemination of information about the 2023 MSME RNRE event by Diskominfotik, namely through news on the website, Instagram and Tiktok. In developing this message, Diskominfotik collaborated with the Instagram accounts @loennagan and @pemkabnara, tiktok @loennagan as well as local media websites, namely Antara Foto, Serambinews, Rakyat Welfare, National Elasi, Indo Satu, Aceh Express, Editorial and Nagan Raya Regency Government.